A Modern Lens: An Analysis of Davenant’s Macbeth Using Lin-Manuel Miranda’s Hamilton (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
This paper uses Miranda's Hamilton to analyze and better understand Davenant's Macbeth from the 17th century. It specifically analyzes the use of music genres, popular culture references, and choreography.For additional context, listen to the author's reflection on the piece below.